THE ROLE OF COMPUTATIONAL LINGUISTICS AND INFORMATION TECHNOLOGY IN DIGITAL LINGUISTICS - Babayeva Gulnozakhan Latibjonovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article talks about the formation of the science of computer linguistics as a result of the positive cooperation of computer technologies and information technology with the science of linguistics.